2005
DOI: 10.1016/j.ssci.2005.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age-related gait adaptations and required coefficient of friction

Abstract: A laboratory study was conducted to evaluate if age-related gait adaptations in walking velocity, step length and heel contact velocity could adversely influence friction demand characteristics (i.e. RCOF) and the likelihood of slip initiation. Additionally, relationship between transitional acceleration of the whole body center-of-mass (COM) and friction demand was assessed between young and older participants. Fourteen younger (7 females and 7 males, 18-30 years old) and 14 older (7 females and 7 males, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 20 publications
6
57
3
1
Order By: Relevance
“…Although implicated, further EMG study is required to understand the relationship between quadriceps fatigue and the co-activation dynamics. Reduction in WV has been identified as a risk factor for slip-induced falls in the elderly [10]. Although implicated, no significant difference in WV was observed in this study.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Although implicated, further EMG study is required to understand the relationship between quadriceps fatigue and the co-activation dynamics. Reduction in WV has been identified as a risk factor for slip-induced falls in the elderly [10]. Although implicated, no significant difference in WV was observed in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Furthermore, Lockhart et al [8] indicated that a reduction in TA is likely to increase the friction demand at the shoe floor interface of the contacting foot. Kim et al [10] found TA and HCV to be predictor variables for RCOF in younger adults. This is in accordance with the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walking trials comprising the slipping and falling trials were conducted on a walking track (20 m), which was elevated 15 cm above the floor surface and consisting of vinyl tile [36]. The slippery surface was located 10m from the deck end.…”
Section: Testing and Evaluationmentioning
confidence: 99%
“…La percepción que los mayores tiene del entorno que les rodea y en espacial del pavimento sobre el que deambulan está condicionado fundamentalmente por sus problemas de visión (en la población estudiada en el artículo llegaban al 80% las personas mayores con problemas de visión), y no tanto por una fricción requerida diferente a la de la gente joven (Kim et al, 2005). La percepción ha de ser tanto propioceptiva como visual.…”
Section: Página 77unclassified